PENERAPAN MODEL TALKING CHIPS UNTUK MENGUKUR HASIL BELAJAR DAN KECERDASAN INTERPERSONAL - Sarifa, Zakiyatu; Wardani, Sri; Sulistyaningsih, Triastuti; Purniawati, Henny (Jurnal Inovasi Pendidikan Kimia, 2021)
The aims of research is to find out the analysis of student learning result and interpersonal intelligence through talking chips learning model. The methods of this research is using experiment. The sample used was XI IPA 1 class and XI IPA 2 at SMA N 2 Kudus with sampling technique based on the consideration of the teacher concerned. The data taking is done using validation sheets, cognitive test instruments, observation sheets, student response questionnaires and documentation. The cognitive analysis results of the experimental class 1 pre-test score was 70 and the post-test was 100 while the experimental class 2 the pre-test score was 70 and the post-test was 95. The results of the affective analysis is the highest aspect of the experimental class 1 were aspects of cooperation while for the experimental class 2 is the aspect of curiosity. The indicators of empathetic processing, team building and listening to other owned by the experimental class students are very good, but the indicators for giving feedback and inquiry and questioning are still not enough and need to be improved. It can be concluded that talking chips learning can improve student learning result and interpersonal intelligence and make students more interested and active during the learning process.